The Role of Women Entrepreneurs in Improving the Performance of MSME - Ni Luh Putu Eka Yudi Prastiwi; Luh Kartika Ningsih; Anak Agung Ngurah Eddy Supriyadinata Gorda (Jurnal Dinamika Manajemen, 2025)
This study aims to analyze how women’s entrepreneurial motivation influences the performance of micro, small, and medium enterprises (MSMEs) in Bali, with a particular focus on the mediating effects of human resource competencies, entrepreneurial mindset, and work-life balance. Using a quantitative approach, data were collected from 115 women entrepreneurs through a structured questionnaire. The sample size was determined by multiplying the number of research indicators by five, following SEM-PLS methodological standards. The results reveal that women’s entrepreneurial motivation significantly improves MSME performance when mediated by enhanced human resource competencies and a proactive entrepreneurial mindset. However, work-life balance does not show a significant mediating effect. These findings highlight that internal factors such as motivation, competence, and mindset are more critical to business success than external life-management factors. This study provides valuable insights for policymakers and development institutions to design empowerment programs emphasizing competency development and mindset transformation to strengthen the sustainability and competitiveness of women-led MSMEs.